The Effect of Applying Model on the Integration of 4 Iddhipàdas towards the Scouts Activities in Prathom Suksa 4-6 students of Ban Luang Nue School, Doi Saket District, Chiang Mai Province - Pheiwchai, Siri; pravitvaranuyut, Phrakru; Pantiya, Poonchai (วารสารสันติศึกษาปริทรรศน์ มจร, 2018)
This dissertation aims to 1) to study the model of integrating of the 4 Iddhipãda (path of accomplishmentor basis for success) with the Scout’s activities 2) to develop the model of integrating the 4 Basis for Success with the Scout’s activities and 3) to study the outcomes of using the Model of the Integration of the 4 Iddhipãdas with Scout’s activities towards the Prathom Suksa 4-6 Students of Ban Luang Nue School, Doi Saket District, Chiang Mai Province. Methodology used in this research is the Experimental Research. The populations consisted of 486 Prathom Suksa 4-6 Students in Ban Luang Nue School, during the 2556 academic year. The results of the study on the development and the efficiency of the Model on the integration of the 4 Iddhipãdasinthe Scout’s Activities based on the FarHiking, and Scout Camping Learning Units based on the concept of the integrating Buddhism into Modern Science, thereby, were found that the Efficiency of the learning unitof E1 / E2 was 88.36 / 86.79, which was the higher than the standard set of 80/80. This was confirmed that the efficiency of learning was also higher than the level pre-test before activities done. That is the results of the study were significantly different at .01 level.